Exclusive Breastfeeding Behavior Analysis Based on Health Belief Model: A Cross-Sectional Study - Yulia Vanda Editia; Bagoes Widjanarko; Ani Margawati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Margorejo District is the sub-district with the lowest exclusive breastfeeding coverage in Pati District in 2020 at 10.4%. One of the reasons for the failure of exclusive breastfeeding in the Margorejo Subdistrict is the advertisement of formula milk to provide formula milk, the mother's belief that her baby will remain healthy even though she is not given exclusive breastfeeding, and the mother's assumption that exclusive breastfeeding is not a natural family planning method. This study aims to analyze the factors that influence exclusive breastfeeding behavior based on the Health Belief Model. Analytical design with a cross-sectional study design with a quantitative approach accompanied by a qualitative approach as support (mixed method). The sample set was 102 mothers using systematic random sampling. Quantitative data were analyzed using the chi-square test and logistic regression. Qualitative data are presented in the form of a narrative. The variables in this study related to exclusive breastfeeding behavior in the Margorejo sub-district were perceptions of vulnerability p-value 0.008, perceived seriousness p-value 0.000, perceived benefits p-value 0.001, perceived barriers p-value 0.000, and cues to action p-value 0.000 (p less than 0.05). Variables that have a joint relationship with exclusive breastfeeding behavior are perceived seriousness p-value 0.004, perceived barriers p-value 0.006, and cues to action p-value 0.024. Abstrak: Kecamatan Margorejo merupakan kecamatan dengan cakupan ASI Eksklusif terendah di Kabupaten Pati tahun 2020 sebesar 10.4%. Kegagalan ASI Eksklusif di Kecamatan Margorejo salah satunya yaitu disebabkan karena iklan susu formula untuk memberikan susu formula, keyakinan ibu bahwa bayinya akan tetap sehat walaupun tidak diberikan ASI Eksklusif, dan anggapan ibu mengenai bahwa ASI Eksklusif bukan merupakan KB alami. Penelitian ini bertujuan untuk menganalisis faktor yang berpengaruh terhadap perilaku pemberian ASI Eksklusif berdasarkan Health Belief Model. Desain analitik dengan rancangan cross–sectional study dengan pendekatan kuantitatif yang disertai dengan pendekatan kualitatif sebagai pendukung (mixed method). Sampel yang ditetapkan sebanyak 102 ibu menggunakan systematic random sampling. Data kuantitatif dianalisis menggunakan uji chi–square dan regresi logistik. Data kualitatif disajikan dalam bentuk narasi. Variabel dalam penelitian ini yang berhubungan dengan perilaku pemberian ASI eksklusif di Kecamatan Margorejo adalah persepsi kerentanan p-value 0.008, persepsi keseriusan p-value 0.000, persepsi manfaat p-value 0.001, persepsi hambatan p-value 0.000, dan cues to action p-value 0.000 (p kurang dari 0.05 ). Variabel yang memiliki hubungan bersama dengan perilaku pemberian ASI eksklusif adalah persepsi keseriusan p-value 0.004, hambatan persepsi p-value 0.006, dan cues to action nilai p-value 0.024.